A VSC Algorithm for Nonlinear System Based on SVM - Zhang, Yibo; Ren, Jia (Bio-Inspired Computational Intelligence and Applications, 2007)
A variable structure control (VSC) algorithm for nonlinear system based on feed-forward and feedback technology is developed. A method based on feed-forward SVM (FFSVM) is brought forward to eliminate external disturbance. In order to reduce difference and to track desired trajectory, a feedback SVM (FBSVM) is introduced into the feed-forward system by adopting VSC algorithm. And so recognition and control designing are combined, and recognition of system is avoided. High track speed and robustness are granted. Simulation shows the effectiveness of the scheme.